SURVEI TINGKAT KONDISI FISIK ANGGOTA PANJAT TEBING MAPALA PELITA TAHUN 2022 - Kusnul Sholikhah; Mokhammad Firdaus; Slamet Junaedi (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2023)
The problems of this researcher are: From the discovery of problems, not all of them are used as problems in this study, therefore from the problem